Disaster Mitigation Management By The Regional Disaster Management Agency (BPBD) In Management of Drought Disaster In West Lombok District - Selamet Jalaludin (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Drought is a natural disaster that can result in reduced water availability which is far below needs. West Lombok Regency is one of the districts in NTB Province that is prone to drought. Based on BPBD data from 2019 to 2021, there are six sub-districts that experience drought every year in West Lombok district. The aim of this research is to examine drought disaster mitigation management in West Lombok Regency. The research method used in this research is a qualitative research approach in analyzing the problems that have been determined. The type of data used is descriptive qualitative data. This research uses George R. Terry's management function as a reference. Based on the research results, the West Lombok Regency BPBD is still encountering obstacles or problems, namely related to organizing, actuating and also monitoring (controlling) the drought disaster in West Lombok Regency. Therefore, when one of the indicators of these management functions is not fulfilled, then the drought disaster mitigation management carried out by the West Lombok BPBD will not be optimal. Supporting BPBD activities consists of internal factors, namely from BPBD and external factors from communities outside BPBD. The inhibiting factors that hinder BPBD activities are 3 aspects, namely road access to the affected areas is still inadequate, the budget for carrying out activities and equipment for implementing the program is still inadequate.